Idiosinkrasi Manuskrip Mushaf Al-Qur'an di Desa Rejoagung Ngoro Jombang - Aini, Adrika Fithrotul (Jumantara: Jurnal Manuskrip Nusantara, 2023)
The historical traces of the spread of Islam throughout the archipelago cannot be separated from the existence of ancient manuscripts, which are one of Indonesia's assets. This paper discusses the study of manuscripts in the form of mushafs of the Qur'an in a village in Jombang district, namely Rejoagung Village. The problem that will be answered in this article is regarding the physical characteristics of the manuscripts of the Al-Qur'an in Rejoagung Village and the idiosyncratic aspects of their textology. Some of the things that the author will examine are the forms of rasm, dabt, and the verse numbering system. The method used is the single manuscript method with critical editions in the study of ancient manuscripts. The result of this research is that this manuscript has a different idiosyncratic style from the Mushaf Al-Qur'an manuscripts in Indonesia. Rasm used is a mixture of usmani and imla'i. The verse termination system does not adhere to a Kufah school of thought, which is familiar in the copying of the Qur'an in the archipelago. This shows that the copyist applied idiosyncrasy in the process of copying. Follow-up research is needed to obtain a description of the different patterns of the process of copying the Al-Qur'an mushaf from various ancient manuscripts spread across Nusantara.